The effects of weight training and endurance swimming on muscle, power, and performance
Five groups of college swimmers were formed and participated in the following activities: endurance weight training with no swimming; power weight training with no swimming; endurance weight training with swimming; power weight training with swimming; and swimming only. They were tested on swim bench activities and 50 and 200 m performances in the pool. Swimming training was early in the fall with the majority of yardage being performed at EN-1 and EN-2 intensity levels. The weight training was low repetition (<6) and high resistance (100-120 lb.). Fatigue ratio, force and power output and performance were estimated. The results are confusing for they do not show any logical pattern. The study contends that basic endurance training should be coordinated with dry-land training to maintain power while an endurance base is established. The reader should be warned that results do not fully support such a conclusion because of the contradictory nature of the specific factor results, the confusing design of the study, and the validity of the measures used for all the treatments considered. Implication: Little should be heeded from this study.